Interferon regulatory factor 1 (IRF1) controls the metabolic programmes of low-grade pancreatic cancer cells. Issue 1 (13th May 2022) - Alfarano, Gabriele; Audano, Matteo; Di Chiaro, Pierluigi; Balestrieri, Chiara; Milan, Marta; Polletti, Sara; Spaggiari, Paola; Zerbi, Alessandro; Diaferia, Giuseppe Riccardo; Mitro, Nico; Natoli, Gioacchino
Abstract : Objective: Pancreatic ductal adenocarcinomas (PDACs) include heterogeneous mixtures of low-grade cells forming pseudoglandular structures and compact nests of high-grade cells organised in non-glandular patterns. We previously reported that low-grade PDAC cells display high expression of interferon regulatory factor 1 (IRF1), a pivotal transcription factor of the interferon (IFN) system, suggesting grade-specific, cell-intrinsic activation of IFN responses. Here, we set out to determine the molecular bases and the functional impact of the activation of IFN-regulated responses in human PDACs. Design: We first confirmed the correlation between glandular differentiation and molecular subtypes of PDAC on the one hand, and the expression of IRF1 and IFN-stimulated genes on the other. We next used unbiased omics approaches to systematically analyse basal and IFN-regulated responses in low-grade and high-grade PDAC cells, as well as the impact of IRF1 on gene expression programmes and metabolic profiles of PDAC cells. Results: High-level expression of IRF1 in low-grade PDAC cells was controlled by endodermal lineage-determining transcription factors. IRF1-regulated gene expression equipped low-grade PDAC cells with distinctive properties related to antigen presentation and processing as well as responsiveness to IFN stimulation. Notably, IRF1 also controlled the characteristic metabolic profile of low-grade PDAC cells, suppressing both mitochondrial respiration and fatty acid synthesis, which may in part explain its growth-inhibiting activity. Conclusion: IRF1 links endodermal differentiation to the expression of genes controlling antigen presentation and processing as well as to the specification of the metabolic profile characteristic of classical PDAC cells.